Multi-Bank Loan Pool Contracts - Andreas Gintschel; Andreas Hackethal (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
We show that multi-bank loan pools improve the risk-return profile of banks' loan business. Banks write simple contracts on the proceeds from pooled loan portfolios, taking into account the free-rider problems in joint loan production. Thus, banks benefit greatly from diversifying credit risk while limiting the efficiency loss due to adverse incentives. We present calibration results that the formation of loan pools reduce the volatility in default rates, proxying for credit risk, of participating banks? loan portfolios by roughly 70% in our sample. Under reasonable assumptions, the gain in return on equity (in certainty equivalent terms) is around 20 basis points annually.
Keywords: 330; Kreditgeschäft; Unternehmenskooperation; Vertrag; Bank; Kreditrisiko; Rentabilität; Theorie